Propuesta urbana para la reubicación de los asentamientos Palmas III y Miraflores, Comuna 10, Neiva (2022)
The current problem that exists in the informal settlements of commune 10 of the municipality of Neiva, is that it not only affects the quality of life of the residents of that sector, but also the development of the city itself. With this statement we be gin this article, to emphasize the settlements that are located in strategically well located areas, which as the years passed were included within the development of the city. According to the research on the settlements of commune 10 of the municipality of Neiva, it was taken into account that there are in this commune a large number of families that currently reside in these informal sectors, counting on a number of urban and social problems, which 3 directly affects the development of these people.